2021
DOI: 10.1021/acs.chemrev.0c01201
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biocatalysis with Chemical Modification and Expanded Amino Acid Alphabet

Abstract: The two main strategies for enzyme engineering, directed evolution and rational design, have found widespread applications in improving the intrinsic activities of proteins. Although numerous advances have been achieved using these ground-breaking methods, the limited chemical diversity of the biopolymers, restricted to the 20 canonical amino acids, hampers creation of novel enzymes that Nature has never made thus far. To address this, much research has been devoted to expanding the protein sequence space via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 625 publications
(1,294 reference statements)
0
79
0
Order By: Relevance
“…Research in the field of reprogrammed protein translation has now reached experimental and intellectual maturity: More than 200 non-canonical amino acids (ncAAs, i.e., a diversity that is an order of magnitude higher than that of the canonical amino acid repertoire) were introduced into proteins via various genetic code expansion routes: Selective pressure incorporation, stop codon suppression (SCS), fragment condensation, protein semisynthesis, and peptidomimetics [ 1 ]. It has been shown that AAs with non-proteinogenic functional groups can be used to manipulate, design, and elucidate protein structure, dynamics, function, allosterism, interactions, catalysis, folding, synthesis, trafficking, degradation, and aggregation [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of reprogrammed protein translation has now reached experimental and intellectual maturity: More than 200 non-canonical amino acids (ncAAs, i.e., a diversity that is an order of magnitude higher than that of the canonical amino acid repertoire) were introduced into proteins via various genetic code expansion routes: Selective pressure incorporation, stop codon suppression (SCS), fragment condensation, protein semisynthesis, and peptidomimetics [ 1 ]. It has been shown that AAs with non-proteinogenic functional groups can be used to manipulate, design, and elucidate protein structure, dynamics, function, allosterism, interactions, catalysis, folding, synthesis, trafficking, degradation, and aggregation [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalysts continue to be explored for consideration as green alternatives to alleviate the environmental issues encountered with the use of methods pertaining to traditional organic chemistry Pagar et al, 2021). Thus, multi-enzyme cascade reactions have garnered attention owing to their elegance (Sperl and Sieber, 2018;Hwang and Lee, 2019;MartĂ­nez-Montero et al, 2019), comprehensiveness, and involvement in the synthesis of a considerable variety of pharmaceuticals, agrochemicals, and other industrially important chemicals (Sung et al, 2018;Patil et al, 2019;Yoon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, protein engineering is needed to improve the enzymatic properties of specific enzymes. Notably, protein engineering techniques, including rational design and directed evolution, mainly rely on mutual mutagenesis of the 20 canonical amino acids (cAAs) ( Pagar et al, 2021 ). The limited building blocks of only 20 cAAs inevitably restrict the improvement of protein properties during protein engineering ( Pagar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, protein engineering techniques, including rational design and directed evolution, mainly rely on mutual mutagenesis of the 20 canonical amino acids (cAAs) ( Pagar et al, 2021 ). The limited building blocks of only 20 cAAs inevitably restrict the improvement of protein properties during protein engineering ( Pagar et al, 2021 ). The function and properties of enzymes are determined by the composition and side chain interactions of the AAs, and the introduction of various noncanonical amino acids (ncAAs) into the field of protein engineering could provide more building blocks for the enzyme molecules ( Pagar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation